Using Presentation Board Media to Improve the Mathematical Communication Skills of Class XI-2 Students of Madani Integrated Model High School on Algebra Function Limit Material - Haerani, Novianti; Sasongko, Luddy Bambang; Lefrida, Rita (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Mathematical communication skills are one of the skills that must be improved in students because before solving a problem and doing reasoning, students need to have mathematical communication skills first, namely the ability to convey mathematical ideas, both verbally and in writing and the ability to understand and accept other people's mathematical ideas, as well as the ability to use symbols, notations, and structures in a mathematical concept. The purpose of this study was to obtain an overview of the improvement of students' mathematical communication skills through collaborative classroom action research methods. As for improving mathematical communication skills in class XI-2 students at SMA Negeri Model Terpadu Madani, the researcher utilized media in the form of presentation boards given to students in groups to train their ability to express ideas and present them to other students in front of the class. Based on the results of the study, the mathematical communication skills of students in the class continued to increase in each cycle given for 6 meetings.